(untitled) (Bangladesh Journal of Botany, 2019)
Genetic diversity among Turkish apple genotypes in Ardahan province was conducted based on cpDNA trnL-F sequences. Apple genotypes were plotted on a phylogenetic tree where Pyrus x bretschneideri was used as the outgroup. The plant samples were collected from different locations and genomic DNA was isolated from healthy and green leaves. For sequence in trnL-F region trnLe and trnFf primers were used. Later obtained DNA sequences were edited using the BioEdit and FinchTV. Sequencing data were analyzed using MEGA 6.0 software. Neighbor joining and bootstrap trees were constructed in order to verify the relationships among the apple genotypes. Phylogenetic tree consisted of two clades. The divergence values of trnL-F sequences differed between 0.000 and 0.005. Average nucleotide composition was 38.3 T, 14.9 C, 31.9 A and 14.9% G. The phylogenetic tree constructed based on trnL-F region sequences was nearly parallel to prior phylogenetic studies on apple genotypes.